Do ewe remember? Comparative foraging behaviour of sheep and alternative livestock species in a spatial memory task - Quail, Megan R.; Fraser, Mariecia D. (Applied animal behaviour science, 2025)
Foraging strategy is fundamentally linked with resource availability and dietary preference. Adaptive feeding behaviours, such as the role of spatial memory when navigating to food sites, are found in wild foraging species. We hypothesised that domesticated livestock species also possess adaptive foraging, with potential interspecies differences in this ability resulting from variations in foraging strategy. As such, this study aimed to compare foraging behaviour, in relation to ability to remember and prioritize food sites of different value, in livestock species that have different dietary preferences and backgrounds: sheep (Ovis aries), goats (Capra hircus) and alpacas (Vicugna pacos). A total of 705 trials were conducted across general training, criterion training and test trials. Eighteen sheep, 10 goats and 7 alpacas were presented with eight identical buckets, positioned on four cross mounts, that were placed into four corners of the test arena. Following acclimation and training, the subjects were required to search the arena for two randomly baited buckets, each of the two buckets containing either the large food reward or small food reward. After locating the reward, the animals re-entered the arena and were tasked to relocate the same buckets (Experiment 1). Each subject was allowed a maximum of two incorrect visits to non-baited buckets per trial, and the trial continued until both baits had been eaten or 7 min of inactivity had passed (more than two errors resulted in a ‘failure’ score for the individual trial). These conditions were then replicated, except that the animal was allowed to make a single selection between the large or small reward following their return to the arena after the initial search (Experiment 2). The goats passed the most trials across all three species (p < 0.001) and made fewer errors when relocating the baited buckets in training and test trials across both experiments (p < 0.05 and p < 0.01, respectively). In contrast, the alpacas failed to pass the training criterion, with the exception of one individual, primarily due to exceeding the time limit for inactivity. We detected no significant difference in preference for the larger food quantity between species in either experiment (p = 0.65 and p = 0.55, respectively). Equally, selection of either quantity did not deviate from random chance across all individuals (except for a single sheep, p < 0.05, Experiment 2). Thus, goats exhibited the greatest spatial memory of the three species across both test conditions, which may reflect the adaptive foraging strategy that is required to navigate patchy distributions of browse in the complex natural habitats of this species. We recommend that further work should be carried out to determine the scale of selectivity and role of habitat perception on grazing distribution in these species. This information could be used to predict how differences in foraging strategy can be exploited to maximise pasture use efficiency in multi-species grazing systems. •The adaptive abilities of sheep, goats, and alpacas were tested in a spatial memory foraging task.•Goats exhibited evidence of superior spatial memory and made fewer errors than other species.•The alpacas showed low capacity to solve the spatial memory task and failed the training criterion.•All animals showed a preference for immediate reward with restricted choice, regardless of value.